Habilidades prelectoras y procesos lectores en niños de 9-10 años de la Unidad Educativa “Dr. Baltazar Aguirre”, parroquia Quinara, periodo lectivo 2023-2024 - Castillo Briceño, Ismenia Custodia (2024)
The following curricular integration work had as its general objective to analyze the influence of pre-reading skills on reading processes in children aged 9 to 10 years of the “Dr. Baltazar Aguirre” Educational Unit; it was a qualitative study, descriptive in scope, non-experimental, and cross-sectional in design. An interview and an observation form were applied to the sample of 2 teachers and 11 students. The results show that students are at an average level in phonological awareness, regular in alphabetical knowledge and short-term memory, and nothing in oral language, which means that they have not yet reached an adequate level in the development of these skills for their age, in addition, they have developed a basic perceptual process, they do not yet have a good ability to perceive stimuli from their environment, in terms of lexical processes some development has been observed but they do not reach an advanced level, since they begin to acquire a good vocabulary and to understand the meanings of words, in the syntactic processes it is evident that they lack development, since they have difficulties in structuring and understanding grammatical rules, and finally in the semantic processes it is identified that they do not show significant progress since they do not achieve the understanding of sentences in different contexts, the need for the design of a didactic guide of activities to strengthen pre-reading skills in children was also evident, in order to provide a resource to help teachers apply these activities with their students. It was concluded that pre- reading skills are essential for the correct development of fluent, clear, and comprehensive reading, which indicates that those children who have not correctly developed pre-reading skills cannot understand, reflect, synthesize, and extract ideas from a text, therefore, their reading processes present deficiencies.